Selective killing of K‐ras–transformed pancreatic cancer cells by targeting NAD(P)H oxidase. Issue 3 (8th April 2015) - Wang, Peng; Sun, Yi‐Chen; Lu, Wen‐Hua; Huang, Peng; Hu, Yumin
Abstract: Introduction: Oncogenic activation of the K ‐ ras gene occurs in >90% of pancreatic ductal carcinoma and plays a critical role in the pathogenesis of this malignancy. Increase of reactive oxygen species (ROS) has also been observed in a wide spectrum of cancers. This study aimed to investigate the mechanistic association between K‐ras –induced transformation and increased ROS stress and its therapeutic implications in pancreatic cancer. Methods: ROS level, NADPH oxidase (NOX) activity and expression, and cell invasion were examined in human pancreatic duct epithelial E6E7 cells transfected with K ‐ ras G12V compared with parental E6E7 cells. The cytotoxic effect and antitumor effect of capsaicin, a NOX inhibitor, were also tested in vitro and in vivo . Results: K‐ras transfection caused activation of the membrane‐associated redox enzyme NOX and elevated ROS generation through the phosphatidylinositol 3′‐kinase (PI3K) pathway. Importantly, capsaicin preferentially inhibited the enzyme activity of NOX and induced severe ROS accumulation in K‐ras –transformed cells compared with parental E6E7 cells. Furthermore, capsaicin effectively inhibited cell proliferation, prevented invasiveness of K‐ras –transformed pancreatic cancer cells, and caused minimum toxicity to parental E6E7 cells. In vivo, capsaicin exhibited antitumor activity against pancreatic cancer and showed oxidative damage to the xenograft tumor cells. Conclusions: K‐ras oncogenic signaling causes increased ROS stress through NOX, and abnormal ROS stress can selectively kill tumor cells by using NOX inhibitors. Our study provides a basis for developing a novel therapeutic strategy to effectively kill K‐ras –transformed cells through a redox‐mediated mechanism.